ANALISA SOFTWARE MANAGER DALAM PROSES MENGHASILKAN INFORMASI LAPORAN KEUANGAN UNTUK UMKM KEDAI KOPI “MAMANK BANGKUY” SAMARINDA 2019 - Achmad Rudzali; Rifadin Noor; Shelly Annisa Aprinda (Jurnal Eksis, 2021)
In the midst of the rise of accounting applications circulating among users, the author takes one of them which was considered the easiest to run. The MANGER application wss relatively easy to use for accounting financial reporting. In addition to the type of MSME business, this application can also be used for college assignments. This study discusses how the MANAGER application could process data and produce financial statement information accurately and quickly. The information would then be analyzed by users who hade accounting skills. In this study, the MANAGER application was applied to SMEs in the culinary field. The result of the information was the condition of the financial position while running the business. The MANAGER output was the values owned by the UMKM business, in the formed of assets owned worth Rp. 172.856.000,-, debt borne by Rp.1500.000.000,-, income of Rp. 3.318.000,-. which must be reduced by the cost of Rp. 462,000,-. So the profit of Rp. 2.856.000,- . This information would be analyzed more deeply as a future business strategy for better prospects. Information is obtained quickly compared to the manual method. The presence of the MANAGER application is very helpful in running a business.Keywords: MSME, MANAGER, output.